Immunization of Wistar female rats with 255-Gy-irradiated Toxoplasma gondii: Preventing parasite load and maternofoetal transmission - Camossi, Lucilene Granuzzio [UNESP]; Fornazari, Felipe [UNESP]; Richini-Pereira, Virginia Bodelao [UNESP]; Silva, Rodrigo Costa da [UNESP]; Ferreira Cardia, Daniel Fontana [UNESP]; Langoni, Hélio [UNESP] (Elsevier B.V., 2014)
Toxoplasmosis, caused by an obligate intracellular protozoan parasite, Toxoplasma gondii, is an worldwide parasitic disease, with significant importance for animal production and considerable impact to the public health. This study was aimed to evaluate the dynamic of the distribution of T. gondii in tissues of female Wistar rats and their puppies tissues, after the immunization by oral rote with irradiated tachyzoites. One week after pregnancy confirmation, rats was challenged by gavage with T. gondii bradyzoites, oocysts or tachyzoites of T. gondii. Forty-eight pregnant rats were grouped as follow: immunized and challenged with bradyzoites (BZ*); non-immunized and challenged with bradyzoites (BZ); immunized and challenged with oocysts (OC*); non-immunized and challenged with oocysts (OC); immunized and challenged with tachyzoites (TZ*); non-immunized and challenged with tachyzoites (TZ); only immunized (I); control group (C). After parturition the rats were sacrificed and the tissues were researched for the DNA of T. gondii by polymerase chain reaction (PCR) and the parasite load determined by the quantitative PCR (qPCR). It was verified that the immunization with irradiated tachyzoites of T. gondii induced the reduction of parasitic load in most organs analyzed, although not prevent the establishment of infection with the parasite. And also, the immunization showed a favorable effect on the birth rate and litter size. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Toxoplasmosis; Immunization; Wistar rats; Parasite load; Zoonosis